2011
DOI: 10.1007/s00442-011-2057-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulated nitrogen deposition affects wood decomposition by cord-forming fungi

Abstract: Anthropogenic nitrogen (N) deposition affects many natural processes, including forest litter decomposition. Saprotrophic fungi are the only organisms capable of completely decomposing lignocellulosic (woody) litter in temperate ecosystems, and therefore the responses of fungi to N deposition are critical in understanding the effects of global change on the forest carbon cycle. Plant litter decomposition under elevated N has been intensively studied, with varying results. The complexity of forest floor biota a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 54 publications
3
46
0
2
Order By: Relevance
“…Though not yet studied in tropical savannas, experiments on wood decomposition frequently indicate sensitivity to scarce or unavailable nutrients (notably nitrogen and phosphorus, e.g., Bebber et al. , Gora et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Though not yet studied in tropical savannas, experiments on wood decomposition frequently indicate sensitivity to scarce or unavailable nutrients (notably nitrogen and phosphorus, e.g., Bebber et al. , Gora et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…N addition has decreased (Fog, 1988;Turunen et al, 2004;Waldrop et al, 2004;Janssens et al, 2010), increased (Mack et al, 2004;Waldrop et al, 2004;Bragazza et al, 2006), or had no effect on (Knorr et al, 2005) SOM decomposition rates. These studies observed increased (Micks et al, 2004;Wal et al, 2007;Allison et al, 2009;Bebber et al, 2011) or level (Mccoll & Powers, 1998) decomposition rates for wood, with no effect on PyOM . These studies observed increased (Micks et al, 2004;Wal et al, 2007;Allison et al, 2009;Bebber et al, 2011) or level (Mccoll & Powers, 1998) decomposition rates for wood, with no effect on PyOM .…”
Section: Introductionmentioning
confidence: 89%
“…The rate of fungal utilisation of colonised wood depends, at least in part, on extra- (Table S1). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 (Bebber et al, 2011). Enzymatic changes and wood decomposition, therefore, mirror specific fungal responses to short-term invertebrate grazing, in soil microcosms.…”
Section: Extracellular Enzyme Productionmentioning
confidence: 95%